Perspectivas dialógicas e decoloniais sobre identidade e formação docente no ensino-aprendizagem de língua inglesa: um estudo autoetnográfico - Lima, Josenice Cláudia Moura de (2020)
This thesis is the result of reflections on my teacher education, through the observation of my teaching practice and the dialogue with the Teaching-Learning process. The methodology is autoethnography (CHANG, 2013), (ELLIS, ADAMS & BOCHNER, 2015) and (BEZERRA, 2019), as it presents a research and writing approach that seeks to describe and analyze a personal experience that leads to the understanding of a cultural experience, considering research as a politically, socially just and conscious act (ELLIS, ADAMS & BOCHNER, 2015). Through this study, I reflect on the following questions: Teacher Education (KLEIMAN, 2006), (IFA, 2006) and (CRUZ, 2016), Teaching Identity (BAUMAN, 2001) and (BAKHTIN, 1993, 2009, 2015), Languages Teaching and Learning in Brazil (FREIRE, 2001, 2004), (CELANI, 2008), (JANKS, 2010) and (STELLA & TAVARES, 2013), and the place of English Language, in a decolonial perspective (STELLA, CAVALCANTI, TAVARES & IFA, 2014). The reflections on decoloniality come from the studies of Quijano (2005), Grosfoguel (2007), Mignolo (2008), and Souza Santos and Menezes (2009). For the development process of this work, I was the teacher researcher in the classrooms I taught and used as data collection means a reflective journal of the research teacher, lesson plans, notes during the classes and texts written by me at the beginning of my work in public schools, fourteen years ago. The discourses present in these materials served as a basis for dialogical data analysis, from a Bakhtinian perspective (BAKHTIN, 1993, 2009, 2015) in dialogue with other authors who deal with the themes present in this work. This research aims to reflect on how I constitute myself as a teacher of English Language and the place of this language in contemporary times and as specific objectives: to understand my process of teacher education, as well as the identity constitution in this process; problematize the discourses about being a teacher within our culture; to analyze how the teaching and learning of English Language takes place, from my view as a researcher, identifying which themes emerge from such discourses and identifying evidence of (de) coloniality in my process as a teacher and researcher. I could see that some themes emerged from such discourses, such as: harm, sharing of the sensitive, disagreement (RANCIERE, 1996). Through this research, I was able to understand, describe and analyze a personal experience that contributes to the understanding of a cultural experience: Teacher Education is genre, because it is a process.